Fallow improvement with forage legumes: Potentials and constraints of an integrative technology for crop-livestock systems in sub-humid West Africa - Muhr, L.; Peters, Michael; Tarawali, Shirley A.; Schultze-Kraft, Rainer (Margraf Verlag, 1998)
Integration of forage legumes into traditional fallow management systems can help to improve both forage supply at a time of feed scarcity and soil fertility. At two sites in south-west Nigeria, 11 legume species with generally low nutrient requirements were evaluated on-station in a short-term ley system with a subsequent maize crop. Eight months after sowing, the forage dry matter yields at both sites were highest for Stylosanthes guianensis (9 t ha<sup(<minus>1)>), Aeschynomene histrix (4 and 7 t ha<sup(<minus>1)>) and Centrosema macrocarpum (3 and 6 t ha<sup(<minus>1)>). Despite dry season forage utilisation, grain yields of subsequently grown maize exceeded those after natural fallow by up to 138 percent (S. guianensis) and 52 percent (Zornia glabra) at the respective sites. In simple on-farm trials managed by settled Fulani farmers, forage yields of the legumes were much lower than on-station, with only S. guianensis showing high potential under farmers' low input management. Despite additional labour demand during the establishment of the legumes, farmers' interest in the innovation grew in the course of the experiment. On-station and on-farm results promise a considerable gain in productivity through improved fallow systems, if establishment problems can be overcome.